Pengaruh Employer Branding Dan Employee Engagement Terhadap Turnover Intention Generasi Z Pada Industri FMCG - Fabriana Puspaning Utami; Tito Siswanto (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
The design used in this research is associative quantitative research, with data collection using field research and literature study. Based on data testing, the results obtained for each variable, namely the employer branding variable (X1), were declared valid based on the outer loading value on all instruments > 0.07, then the value obtained in the Average Variance Extracted (AVE) showed a value > 0.5, then on the composite reliability value shows the results > 0.7 and the Cronbach's alpha value is > 0.6. The employee engagement variable is declared valid based on the outer loading value on all instruments is > 0.7, then the value obtained in the Average Variance Extracted (AVE) shows a value > 0.5, then the composite reliability value shows the result > 0.7 and Cronbach's alpha value is > 0.6 . The turnover intention variable is declared valid based on the outer loading value on all instruments is > 0.07, then the value obtained in the Average Variance Extracted (AVE) shows a value > 0.5, then the composite reliability value shows the results > 0.7 and Cronbach's alpha value is > 0.6. Then based on testing the path coefficient value on the employer branding variable on turnover intention, the original sample value was -0.376, and the t-statistic value was 3.481. Employee engagement variable on turnover intention, the original sample value is -0.321 with a t-statistic value of 2.409. Furthermore, based on the results of the calculation of Fcount, a value of 24,361 is obtained. So it can be stated that there is a strong or significant influence between employer branding and employee engagement on the turnover intention of Generation Z in the FMCG industry.